2020
DOI: 10.1108/rpj-07-2019-0191
|View full text |Cite
|
Sign up to set email alerts
|

Orthotropic properties of cement-filled polyamide 12 manufactured by selective laser sintering

Abstract: Purpose The cement-filled PA12 manufactured by selective laser sintering (SLS) offers desirable mechanical properties; however, these properties are dependent on several fabrication parameters. As a result, SLS prototypes may exhibit orthotropic mechanical properties unless properly oriented in build chamber. This paper aims to evaluate the effects of part build orientation, laser energy and cement content on mechanical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Among previous fillers, carbon fibers are known for their high stiffness, high tensile strength, chemical and wear resistance, high thermal conductivity and low thermal expansion, and low weight. Further, as the properties of objects prepared by the SLS process are orientation-dependent [1,2], reinforcing the SLS thermoplastic powders with short CFs enhances the homogeneity of manufactured parts significantly [3,4], and improves the wear resistance of carbon fiber-reinforced composites [5,6]. Accordingly, CFs have been used as a reinforcement for thermoplastic composites used in automotive, motorsport, aerospace, and military industries [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Among previous fillers, carbon fibers are known for their high stiffness, high tensile strength, chemical and wear resistance, high thermal conductivity and low thermal expansion, and low weight. Further, as the properties of objects prepared by the SLS process are orientation-dependent [1,2], reinforcing the SLS thermoplastic powders with short CFs enhances the homogeneity of manufactured parts significantly [3,4], and improves the wear resistance of carbon fiber-reinforced composites [5,6]. Accordingly, CFs have been used as a reinforcement for thermoplastic composites used in automotive, motorsport, aerospace, and military industries [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of fiber-reinforced polymer composites are extremely sensitive to fiber weight fraction, fiber length, fiber orientation, fiber preprocessing, and fiber/matrix adhesion [9,10]. As the properties of SLS-fabricated parts are orientationdependent [11][12][13], it was found that reinforcement with either particles or short fiber enhances the homogeneity of polymer composites prepared by the SLS process [14,15], while introducing long or continuous fibers as a reinforcement results in directional properties of the fibrous composite [9]. Further, the ease with which short fibers are processed saves manufacturing costs considerably, making them most suitable for the reinforcement of polymer matrices in additive manufacturing processes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Next to the AM of inorganic materials [ 2 , 3 ], laser-based powder bed fusion of organic polymers (LB-PBF-P, according to ISO/ASTM 52911-2:2019) has experienced increased interest in terms of research and development over the last decade [ 4 ]. However, AM still requires a lot of operator know-how as many external and internal variables influence the process, e.g., feedstock material [ 5 ] or build orientation [ 6 ]. In this regard, the interplay of parameters related to the laser source, such as laser power, laser beam diameter, laser scanning speed, and hatch distance, with machine-related parameters, such as powder layer height, process temperature, and recoating speed, is crucial for the successful manufacture of dimensionally accurate three-dimensional parts.…”
Section: Introductionmentioning
confidence: 99%